Managerial quality and worker productivity in developing countries - Achyuta Adhvaryu (IZA World of Labor, 2018)
Productivity differences across firms and countries are surprisingly large and persistent. Recent research reveals that the country-level distributions of productivity and quality of management are strikingly similar, suggesting that management practices may play a key role in the determination of worker and firm productivity. Understanding the causal impacts of these practices on productivity and the effectiveness of various management interventions is thus of primary policy interest.
Keywords: L2; M2; O14; O32; O33; 330; managerial quality; worker productivity; labor relations